44 Regional Molecular And Cellular Differences In The Female Rabbit Achilles Tendon Complex. (5th September 2014) - Huisman, Elise; Andersson, Gustav; Scott, Alex; Reno, Carol; Hart, David; Thornton, Gail
Abstract : Introduction: Tendons or regions within a tendon are subjected to tension, compression, friction or a combination thereof. The first aim of this study was 1 to analyse the morphology and expression of extracellular matrix genes in six different regions of the Achilles tendon complex of intact normal rabbits. Men and women experience tendon conditions/injuries with different frequency (Cook, 2007; Cook, 1998; Taunton, 2002). Oestrogen receptors or their transcripts have been detected in human muscles (Wiik, 2009), ligaments (Liu, 1996) and rabbit tendons (Hart, 1998; 2005), making hormones a potential influencer of tendon injury and healing. The second aim 2 was to assess the effect of ovariohysterectomy (OVH) on the regional expression of these genes. Methods: Female New Zealand White rabbits were divided in two groups 1 intact normal rabbits (n = 4) and 2 OVH rabbits (n = 8). For each rabbit, the Achilles tendon complex was dissected into six regions: distal gastrocnemius (DG), distal flexor digitorum superficialis (DFDS), proximal lateral gastrocnemius (PLG), proximal medial gastrocnemius (PMG), proximal flexor digitorum superficialis (PFDS), and paratenon. For each of the regions, hematoxylin and eosin staining was performed for histological evaluation of intact normal rabbit tissues and mRNA levels for proteoglycans, collagens and genes associated with collagen regulation were assessed by RT-qPCR for both the intact normal and OVH rabbit tissues. Results: The distal regions displayed a more fibrocartilaginous phenotype. For intact normal rabbits, aggrecan mRNA expression was higher in the distal regions of the Achilles tendon complex compared to the proximal regions. Collagen Type I and MMP-2 expression levels were increased in the PLG compared to the DG in the intact normal rabbit tissues. The tendons from OVH rabbits had lower gene expressions for the proteoglycans aggrecan, biglycan, decorin and versican compared to the intact normal rabbits, although the regional differences of increased aggrecan expression in distal regions compared to proximal regions persisted. Discussion: The tensile and compressive forces experienced in the examined regions may be related to the regional differences found in gene expression. The lower mRNA expression of the genes examined in the OVH group confirms a potential effect of systemic oestrogen on tendon. References: Cook, et al . Clin J Sport Med. 1998;8:73–77 Cook, et al . Tendinopathy in Athletes (pp. 10–28). Blackwell Publishing, 2007 Hart, et al . Clin Orthop Rel Res .1998;351:44–56, 1998 Hart, et al . Tendon Injuries : Basic Science and Clinical Medicine (pp. 40–48). Springer- Verlag. 2005 Liu, et al . J Orthop Res . 1996;14:526–533 Taunton, et al . Br J Sports Med. 2002;36:95–101 Wiik, et al . Histochem Cell Biol . 2009;131:181–189